Reading and the Making of Student Activists in Soweto, c. 1968-1976 - Mukonde, Kasonde Thomas (My University, 2020)
Abstract This research report explores the reading practices among politically aware high school students living in Soweto between 1968 and 1976. The research report uses original oral interviews as well as archival work to construct a social history of reading. After outlining the social characteristics of schooling in Soweto during these years, the dissertation uncovers networks of reading. The analysis of reading practice draws from the literature of history and sociology of the book in Africa. While black student protest movements in 1970s South Africa have been studied in some depth, the aspect of reading has not been covered systematically. The report builds upon the work of Archie Dick whose book The Hidden History of South Africa’s Book and Reading Cultures uncovers the reading history of common readers in South Africa, ranging from slaves in the Cape Colony to political exiles in the closing years of apartheid. Inspired by The Hidden History’s broad sweep of South African reading history among common readers, the research report focuses on a subset of these - student activists. During this time, the African National Congress and Pan African Congress were banned and the Black Consciousness Movement (BCM), along with their ideology, was hegemonic in the townships. The dissertation uses Dan Magaziner’s and Ian Macqueen’s work on the development of the BCM, primarily as an intellectual movement, and how these ideas were spread in society, to trace the change in reading practices among students in the early 1970s. The research report reveals that Black Consciousness, while not causing the 1976 student uprising, had a decisive effect on the interpretive modes that students employed in their reading, thus opening up a new way of interacting with print. The dissertation also uses Lefebvrian theory to explain how the subversive use of certain spaces such as libraries and community centres, provided by the state, helped forge this new radical perspective on text among students.The major findings of this research report are that (a) most of the reading that student activists did in Soweto in the early 1970s was not overtly political but they had developed counter-hegemonic interpretive modes that subverted texts provided by the state , (b) the BCM successfully penetrated schools with their message and had an important influence on reading practices, (c) students and other community members appropriated spaces such as stateprovided community centres and libraries to further their goals and values and that (d) a social history of reading among common readers such as students can tell us a lot about a time that has otherwise been understood as politically quiescent.
A research report submitted in partial fulfilment of the degree of Master of Arts in History at the University of the Witwatersrand, Johannesburg.